The Role of Guidance and Counseling in Students' Learning Problems at School - Yulianti, Yulianti; Zubaidah, Zubaidah; Amalianita, Berru; Sarman, Freddi (International Journal of Education, Management, and Technology, 2024)
This study intends to explore the role of guidance and counseling in addressing student learning problems at school. The method chosen for this article is Literature Review. The method in this research is using a literature review approach. A literature review is a study that has the aim of searching and analyzing in a comprehensive, structured, without doubt and may be repeated process. This approach is used because of similarities and relevance in systematically assessing all studies related to the role of guidance and counseling in schools. This research consists of 5 articles starting from 2019-2023. Based on the study analysis, it shows that guidance and counseling have a significant role in helping students overcome various learning problems, such as academic difficulties, low motivation, interpersonal conflicts, and others. A holistic approach based on individual needs can provide effective support for students in developing their potential optimally. The implication of these findings is the need to increase the role and support for counselors and teachers in providing quality guidance and counseling services in educational institutions. It is hoped that this study will be able to contribute to improving the understanding and practice of guidance and counseling in schools in order to develop learning outcomes and achievements for the welfare of students.